The First Hundred Years of Mikhail Bakhtin - Emerson, Caryl (Book collections on Project MUSE., 1997)
A foremost Bakhtin authority, Caryl Emerson mines extensive Russian sources to explore Bakhtin's reception in Russia, from his earliest publication in 1929 until his death, and his posthumous rediscovery. After a reception-history of Bakhtin's published work, she examines the role of his ideas in the post-Stalinist revival of the Russian literary profession, concentrating on the most provocative rethinkings of three major concepts in his world: dialogue and polyphony; carnival; and "outsideness," a position Bakhtin considered essential to both ethics and aesthetics. Finally, she speculates on the future of Bakhtin's method, which was much more than a tool of criticism: it will "tell you how to teach, write, live, talk, think."